2019
DOI: 10.1007/978-1-4939-9784-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Videomicroscopy and Semiautomated Analysis of Brain Cell Culture Models of Trinucleotide Repeat Expansion Diseases

Abstract: Real-time monitoring of brain cell models of trinucleotide expansion diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…We next asked if the lower cell index of DMSXL astrocytes could be a consequence of modified cell-substrate interactions. We plated primary DMSXL or WT astrocytes and monitored their adhesion and spreading by live cell videomicroscopy 28 . To exclude the confounding effect of different starting cell numbers, we first confirmed that the cell density of DMSXL and WT cultures was identical 45 min after plating (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next asked if the lower cell index of DMSXL astrocytes could be a consequence of modified cell-substrate interactions. We plated primary DMSXL or WT astrocytes and monitored their adhesion and spreading by live cell videomicroscopy 28 . To exclude the confounding effect of different starting cell numbers, we first confirmed that the cell density of DMSXL and WT cultures was identical 45 min after plating (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The column flow-through, containing mainly astrocytes, was cultured for 14 DIV in astrocyte medium, to further enrich this cell type, eliminate contaminating cells and promote astroglia differentiation. This method allows the establishment of primary cell cultures with a degree of purity of at least ∼90% ( Braz et al, 2020 ), which we assessed by the immunostaining of proteins markers specifically enriched in neurons (TUBB3), oligodendroglia (OLIG2), oligodendrocytes (MBP), and astrocytes (GFAP).…”
Section: Resultsmentioning
confidence: 99%
“…Primary dissociated cell cultures of mouse cortical neurons, astrocytes, and oligodendrocytes were produced as previously described ( Braz et al, 2020 ). Astrocyte precursors were extracted by magnetic cell sorting with magnetic anti-ACSA-2 microbeads (Miltenyi, 130-097-678), following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next asked if the lower cell index of DMSXL astrocytes could be a consequence of modi ed cellsubstrate interactions. We plated primary DMSXL or WT astrocytes and monitored their adhesion and spreading by live cell videomicroscopy 26 . To exclude the confounding effect of different starting cell numbers, we rst con rmed that the cell density of DMSXL and WT cultures was identical 45 minutes after plating (Fig.…”
Section: Dmsxl Astrocytes Show Abnormal Growth Dynamics Reduced Cell ...mentioning
confidence: 99%